Multiple oestradiol functions inhibit ferroptosis and acute kidney injury - Tonnus, Wulf; Maremonti, Francesca; Gavali, Shubhangi; Schlecht, Marlena Nastassja; Gembardt, Florian; Belavgeni, Alexia; Leinung, Nadja; Flade, Karolin; Bethe, Natalie; Traikov, Sofia; Haag, Anne; Schilling, Danny; et al. (Nature, 2025)
Acute tubular necrosis mediates acute kidney injury (AKI) and nephron loss1, the hallmark of end-stage renal disease2-4. For decades, it has been known that female kidneys are less sensitive to AKI5,6. Acute tubular necrosis involves dynamic cell death propagation by ferroptosis along the tubular compartment7,8. Here we demonstrate abrogated ferroptotic cell death propagation in female kidney tubules. 17β-oestradiol establishes an anti-ferroptotic state through non-genomic and genomic mechanisms. These include the potent direct inhibition of ferroptosis by hydroxyoestradiol derivatives, which function as radical trapping antioxidants, are present at high concentrations in kidney tubules and, when exogenously applied, protect male mice from AKI. In cells, the oxidized hydroxyoestradiols are recycled by FSP19,10, but FSP1-deficient female mice were not sensitive to AKI. At the genomic level, female ESR1-deficient kidney tubules partially lose their anti-ferroptotic capacity, similar to ovariectomized mice. While ESR1 promotes the anti-ferroptotic hydropersulfide system, male tubules express pro-ferroptotic proteins of the ether lipid pathway which are suppressed by ESR1 in female tissues until menopause. In summary, we identified non-genomic and genomic mechanisms that collectively explain ferroptosis resistance in female tubules and may function as therapeutic targets for male and postmenopausal female individuals.
Online veröffentlicht: 13. August 2025
Gesehen am 30.10.2025